Angola: Nationalist Narratives and Alternative Histories - Ball, Jeremy; Gastrow, Claudia (Kronos: Southern African Histories, 2019)
It has been over forty years since Angolan independence and yet Angolans have not had many public opportunities to reflect on the past. The end of the country’s civil war was accompanied by a peace agreement that granted a blanket amnesty to all those involved in the conflict. Unlike in South Africa or Rwanda, there have been few officially enacted spaces for ordinary citizens to recount their experiences, nor legal opportunities to seek reparation. State-sanctioned narratives play down divisions among Angolan nationalists before and after independence. Public commemoration avoids seemingly ‘contentious’ issues such as the civil war and tends to focus on military victories over colonialism and foreign interventions. Much of this memory landscape attempts to enforce a hegemonic vision of the past that reinforces the primary position of the ruling MPLA’s (Popular Movement for the Liberation of Angola) centrality as the only legitimate ruler of Angola. It also seeks to locate politics in officially sanctioned arenas of action. Nevertheless, there has been increasing questioning of MPLA narratives seen in everyday attempts to reclaim and rethink controversial events and leaders, and a pushing against arguments that the political is defined by parties and mass organisations.